The co-occurrence of ingroup and outgroup prosociality across 121 societies - Kasper Otten (Proceedings of the National Academy of Sciences, 2026)
In an increasingly interconnected world, prosociality across group boundaries becomes ever more important. Yet, a common premise in the behavioral and social sciences is that people are prosocial mainly toward their ingroup and not outgroups. So far, evidence for this premise comes mostly from studies in which people must choose between ingroup and outgroup prosociality, thereby precluding positive associations between the two types of prosociality. We study situations in which people make separate decisions regarding the ingroup and outgroup, allowing us to examine how ingroup and outgroup prosociality are related. Across six large-scale and cross-societal datasets spanning 743,402 individuals in 121 societies, we find a robust positive relationship between ingroup and outgroup prosociality. This relationship holds across societies, different group categorizations, and a diverse range of prosociality measures, including prisoner’s dilemmas, public good dilemmas, dictator games, and survey items on trust and tolerance. Although people are slightly more prosocial toward their ingroup than the outgroup, those who are prosocial toward the ingroup also tend to be prosocial toward the outgroup. The results offer an optimistic message for prosociality across group boundaries. When people are not made to choose between the ingroup and outgroup, they are generally prosocial toward both.